2022
DOI: 10.3389/fonc.2022.951215
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety profile of COVID-19 mRNA vaccine in patients with hematological malignancies: Systematic review and meta-analysis

Abstract: Patient populations, including those with hematological malignancies, have different responses to COVID-19 vaccines. This study aimed to quantitatively analyze the efficacy and safety of COVID-19 mRNA vaccines in patients with hematological malignancies. Studies reporting on the efficacy and safety of COVID-19 mRNA vaccines in cohorts with hematological malignancies compared to healthy controls were systematically searched in four databases. Meta-analysis and subgroup analyses were performed to generate quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Vaccination with three–four doses and to a lesser extent with two doses was protective against this event. These results are in line with previous evidence on HM patients who could benefit from additional doses of vaccine in the development of a more effective humoral and T‐cell‐mediated immune response 3–5,24–26 . Moreover, our study confirmed that viral shedding in these patients can be prolonged, especially in elderly patients and in those treated for NHL and CLL.…”
Section: Discussionsupporting
confidence: 91%
“…Vaccination with three–four doses and to a lesser extent with two doses was protective against this event. These results are in line with previous evidence on HM patients who could benefit from additional doses of vaccine in the development of a more effective humoral and T‐cell‐mediated immune response 3–5,24–26 . Moreover, our study confirmed that viral shedding in these patients can be prolonged, especially in elderly patients and in those treated for NHL and CLL.…”
Section: Discussionsupporting
confidence: 91%
“…Detectable B cells (at least 40/mm 3 ) and a long time since the last exposure to rituximab have been associated with the development of anti-SARS-CoV-2 spike protein antibodies after the booster vaccine [ 19 , 20 ]. Additional questions relate to the policy of vaccination against COVID-19, especially for patients with hematological malignancies who have shown a heterogeneous response to vaccination as mentioned in a recent meta-analysis and subgroup analyses [ 21 ]. According to the OnCovid registry, vaccination against SARS-CoV-2 was associated with a decrease in morbidity and mortality related to COVID-19 in cancer patients including 346 patients with hematological malignancies [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional questions relate to the policy of vaccination against COVID-19, especially for patients with HM who have shown a heterogeneous response to vaccination as mentioned in a recent meta-analysis and subgroup analyses (17). According to the OnCovid registry, vaccination against SARSCoV-2 was associated with a decrease in morbidity and mortality related to COVID-19 in cancer patients including 346 patients with HM (18).…”
Section: Discussionmentioning
confidence: 99%